TRANSKRYPCJA ROZMYŚLANIA PRZEMYSKIEGO A SPOSÓB MYŚLENIA O SKŁADNI TEKSTU - STRAMCZEWSKA, Olga (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
The article’s author turns to the example of Rozmyślanie przemyskie in order to demonstrate how transcriptions of text were affected by editors’ opinions on the Polish syntax of the 15th century. At the same time, the transcription inﬂuenced opinions of the readers. To this end, selected elements of two different transcriptions of Rozmyślanie przemyskie have been compared, namely excerpts from Chrestomatia staropolska and the equivalent excerpts from the version edited by Wacław Twardzik and Feliks Keller. Special attention has been paid to issues related to sentence delimitation in the transcription, which strongly affects the image of the 15th century Polish syntax reﬂected in the speciﬁc historical editions. Supplements to the text, introduced by editors and inspired by source suggestions, have also been submitted to a syntax analysis. The same holds true for conjunctions and prepositions “extracted” from the onsets or the codas of words included in the Freiburg edition. Both editions present different pictures of the historical text’s syntax which stemmed from their editors’ varying approaches to the text. Therefore, depending on the actual edition, the reader will be provided with different answers to the following key questions revolving around Polish syntax: what type of predicate combinations prevailed?; how strong was the predicative nature of participle constructs?; how long were the sentences?
The transcription of Rozmyślanie Przemyskie in the context of viewing text syntax
Keywords: ruled of editing Old Polish texts; Rozmyślanie przemyskie; transcription; historical syntax